Factors Related to Ability and Willingness to Pay Health Insurance in Non-Wage Workers - Tuan, Yuni Yarti; Dodo, Dominirsep O. (Universitas Nusa Cendana, 2023)
The target for participation in the National Health Insurance 2024 is 98%. All residents are required to participate by paying contributions directly or indirectly/borne by the government. There are still residents, especially non-wage earner workers, who are considered economically capable and willing to pay contributions independently but have yet to participate as participants. It was also found that many participants were in arrears when paying their fees. This research wants to analyze factors related to the ability and willingness to pay in groups of non-wage earners. This research was a quantitative study with a cross-sectional design. The research results showed a relationship between employment, income, expenses, and the number of family members with the ability to pay. Knowledge and information about health insurance policies were related to willingness to pay. The sub-district government needs to carry out outreach and education about the national health insurance policy, especially regarding the rights and obligations of participants, and improve the selection mechanism and economic suitability of potential recipients for contribution assistance.